Edukasi Kesehatan Reproduksi Remaja Pada Masa Pandemi Covid-19 di Kabupaten Tabanan Tahun 2020 - Sariyani, Made Dewi; Ariyanti, Kadek Sri; Winangsih, Rini; Pemayun, Cokorda Istri Mita (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2020)
Reproductive health is a problem that needs special attention, especially among adolescents. Every teenager should have excellent reproductive health, so that they can produce a healthy and quality generation. Adolescence is a period of rapid development in the journey of human life. Adolescent problems can occur in connection with different needs and self-actualization of the environment in which they live. In order to foster healthy adolescent living behavior, it is necessary to care in the form of services and provision of information as well as mutual understanding of the importance of adolescent reproductive health. In the Covid-19 Pandemic situation, education is carried out online. Increasing adolescent knowledge about reproductive health. The knowledge of adolescents increases to form healthy adolescents who are responsible for their reproductive health independently. Conducting pre and post tests to determine changes in adolescent knowledge after education. The educational participants were 205 high school students in Tabanan Regency. The percentage of adolescents who knew about reproductive health before education was 91% and after education was 98%. There is a change in the percentage of adolescent knowledge before and after being given education. Educational methods are effective in increasing adolescent knowledge about reproductive health. It is necessary to increase adolescent reproductive health education activities to form adolescents who are disciplined and responsible for their reproductive health independently.ABSTRAKKesehatan reproduksi merupakan masalah yang perlu mendapatkan perhatian khusus terutama di kalangan remaja. Setiap remaja hendaknya memiliki kesehatan reproduksi yang prima, sehingga dapat menghasilkan generasi yang sehat dan berkualitas. Masa remaja merupakan masa terjadinya perkembangan pesat dalam perjalanan hidup manusia. Problematika remaja dapat terjadi sehubungan dengan perbedaan kebutuhan dan aktualisasi diri terhadap lingkungan tempat hidupnya. Dalam rangka menumbuhkembangkan perilaku hidup sehat remaja, maka perlu kepedulian dalam bentuk pelayanan dan penyediaan informasi serta kesepahaman bersama akan pentingnya kesehatan reproduksi remaja. Dalam situasi Pandemi Covid-19, maka edukasi dilakukan secara daring. Meningkatkan pengetahuan remaja tentang kesehatan reproduksi. Pengetahuan remaja meningkat untuk membentuk remaja yang sehat dan bertanggungjawab atas kesehatan reproduksinya secara mandiri. Melakukan pre dan post test guna mengetahui perubahan pengetahuan remaja setelah dilakukan edukasi. Peserta edukasi adalah remaja siswa SMA di Kabupaten Tabanan yang berjumlah 205 orang. Persentase remaja yang tahu tentang kesehatan reproduksi sebelum dilakukan edukasi sebesar 91% dan setelah edukasi sebesar 98%. Terdapat perubahan persentase pengetahuan remaja sebelum dan setelah diberikan edukasi. Metode edukasi efektif untuk meningkatkan pengetahuan remaja tentang kesehatan reproduksi. Perlu ditingkatkan kegiatan-kegiatan edukasi kesehatan reproduksi remaja untuk membentuk remaja yang disiplin dan bertanggungjawab terhadap kesehatan reproduksinya secara mandiri.